EVALUASI LUASAN KAWASAN MANGROVE UNTUK MENDUKUNG PERIKANAN UDANG DI KABUPATEN CILACAP PROVINSI JAWA TENGAH (Evaluation of the Mangrove Area Extents to Support Fishing Shrimp in Cilacap Regency, Central Java Province) - Triono P Pangesti; Tri Wiji Nurani; Eko Sri Wiyono (Bogor Agricultural University, 2012)
ABSTRACTCilacap waters are rich with shrimp resource, particularly from Penaidae spp species, such as shrimp Jerbung (Penaeus merguensis) and shrimp Dogol (Metapenaeus endevouri and Metapenaeus ensis). Statistic data of shrimp in Cilacap showed shrimp production keep on declining, from 1,118,644 kg in 2004 to 818,595 kg in 2008. The declining production is suspected due to the increasing intensity of catching and the damage of ecology in coastal areas, particularly the mangrove. This research is aimed at mapping the mangrove areas, and estimating stock of shrimp resource in Cilacap. Data analysis was conducted by using spatial analysis and analysis of potential resource of fish. Results of the analysis showed that estimated mangrove forest in Cilacap in 2005 was about 14,502.55 ha, reduced to about 9,326.71 ha in 2007 and continue to decline to about 2,618.78 ha in 2009. Estimated score of MSY shrimp is 955,493.34 kg/year, with optimum catch 55,014.68 trips.Keywords: analysis of surplus production, Cilacap, mangrove, shrimp, spatial analysis——ABSTRAKWilayah perairan Kabupaten Cilacap kaya akan sumberdaya udang, khususnya dari jenis Penaidae spp., diantaranya yaitu udang jerbung (Penaeus merguensis) dan udang dogol (Metapenaeus endevouri dan Metapenaeus ensis). Data statistik perikanan udang di Cilacap menunjukkan produksi udang terus mengalami penurunan yaitu dari 1.118.644 kg pada tahun 2004 menjadi 818.595 kg pada tahun 2008. Penurunan produksi udang di Cilacap diduga disebabkan oleh meningkatnya intensitas penangkapan dan kerusakan ekologi kawasan pesisir, khususnya hutan mangrove. Penelitian ini bertujuan untuk menyusun peta untuk menghitung luas kawasan lahan mangrove, dan mengestimasi stok sumberdaya udang di Kabupaten Cilacap. Analisis data dilakukan dengan menggunakan analisis spasial dan analisis potensi sumberdaya ikan. Hasil analisis menyatakan bahwa estimasi luasan kawasan hutan mangrove di Cilacap pada tahun 2005 sekitar 14.502,55 ha, menurun menjadi sekitar